Factors affecting extrusion characteristics of expanded starch‐based products - Mohamed, Suhaila (Wiley Blackwell, 1990)
Effect of feed moisture, oil, protein, sugar, salt, grain size and barrel screw speed on expansion index, torque, pressure, texture, output and final moisture of extruded puffed products were studied. Sugar, salt, and oil improved expansion of the product. Increased feed moisture, protein, sugar, salt and barrel screw speed favorably decreased the torque or pressure in the extruder, and improved the texture of the product. the final moisture in the product was only related to the feed moisture and oil content of the raw material. Reducing grain size increased the expansion, hardness and output of the product and reduced the extruder pressure. All these factors probably influenced the extrusion characteristics of expanded products by affecting the starch‐starch interaction. Viscosity studies on the expanded starch indicated that water, protein and sugar decreased the dextrinization of the starch during puffed extrusion, while salt increased the dextrinization.